Reasons for Acceptance of Improved Potato Varieties by Smallholder Producers. Issue 4 (3rd July 2016) - Nigussie, Zerihun; Alemayehu, Getachew; Adgo, Enyew; Tewodros, Yoseph; Freyer, Bernhard
ABSTARCT: It may be that improved cultivars can increase yield. This project was undertaken to determine factors affecting adoption of new potato ( Solanum tuberosum L.) cultivars over those currently in use. A logistic regression procedure was used to examine factors influencing adoption of improved potato varieties by smallholder farmers. Data were collected with questionnaires administered to 158 respondents. The logit model initially contained 13 factors, of which seven had significant effects on adoption of improved potato varieties. The estimated chi-square value (χ 2 = 31.91) indicated that the data fit the model reasonably well. Partial effects analysis indicated that, compared to those who do not use fertilizer, those who do are younger; have more extension contacts and access to credit, and likely plan to allocate more land to growing potato. Those who belong to an agricultural cooperative are more likely to adopt improved potato varieties. Social, economic, and institutional factors have implications for stakeholders who might adopt or extend use of improved potato varieties.